2013
DOI: 10.1155/2013/720589
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Soil Organic Carbon for Ethiopian Highlands Using Soil Spectroscopy

Abstract: Soil spectroscopy was applied for predicting soil organic carbon (SOC) in the highlands of Ethiopia. Soil samples were acquired from Ethiopia's National Soil Testing Centre and direct field sampling. The reflectance of samples was measured using a FieldSpec 3 diffuse reflectance spectrometer. Outliers and sample relation were evaluated using principal component analysis (PCA) and models were developed through partial least square regression (PLSR). For nine watersheds sampled, 20% of the samples were set aside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 41 publications
1
15
0
1
Order By: Relevance
“…The study by Hassine et al (2008) concluded that SOC content does not exceed 2 % in north-western Tunisia; our prediction model falls within this amount with a maximum organic carbon percentage of 1.2 %. This state of low SOC in soils used for agriculture, compared to forests -which have little indication of soil degradation -has been confirmed by various authors (Arrouays et al, 1994;Cerri, 1988;Robert, 2002). This low content has negative impacts on the soil structure, which is built mainly by means of mineral colloids; its stability is affected, leading to numerous deficiencies in production and susceptibility to degradation factors.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The study by Hassine et al (2008) concluded that SOC content does not exceed 2 % in north-western Tunisia; our prediction model falls within this amount with a maximum organic carbon percentage of 1.2 %. This state of low SOC in soils used for agriculture, compared to forests -which have little indication of soil degradation -has been confirmed by various authors (Arrouays et al, 1994;Cerri, 1988;Robert, 2002). This low content has negative impacts on the soil structure, which is built mainly by means of mineral colloids; its stability is affected, leading to numerous deficiencies in production and susceptibility to degradation factors.…”
Section: Discussionmentioning
confidence: 52%
“…Thus, methods are needed for fast and inexpensive prediction of important soil quality indicators such as SOC. The potential of diffuse reflectance spectroscopy in the visible and near-infrared (VNIR) range for fast prediction of soil properties in a non-destructive and efficient way has been demonstrated by a number of studies (Amare et al, 2013;Shiferaw and Hergarten, 2014;Shepherd and Walsh, 2002).…”
mentioning
confidence: 99%
“…Detailed overview of different techniques employed in modern times for SOC determination is well presented by Chatterjee et al (2009). Despite the wide usage of the "traditional" Walkley and Black (WB) method, due to its procedural simplicity (Wang et al 2012), it has been heavily criticized due to its limitations, which include incomplete combustion, variations in oxidation of various forms of SOC by dichromate, high cost of chemicals used for the analysis, and considerable low efficiency in C determination (FAO 2001(FAO , 2007Gelman et al 2012;Amare et al 2013;Gebeyehu et al 2017). Nevertheless, more accurate, precise, and cost-effective measurement of SOC is required in C sequestration programs in terrestrial ecosystems in view of ensuring accurate quantification, verification, and monitoring of potential SOC stocks over time.…”
Section: Uncertainties In Soil Organic Carbon Studiesmentioning
confidence: 99%
“…Thus, methods are needed to allow fast and inexpensive prediction of important soil quality indicators such as SOC. The potential of diffuse reflectance spectroscopy in the visible and near infrared (VNIR) range for fast prediction of soil properties in a non-destructive and efficient way has been demonstrated in a number of studies (Amare et al, 2013, Shiferaw and Hergarten, 2014, Shepherd and Walsh, 2002.…”
Section: Soil Analysis and Spectral Librarymentioning
confidence: 99%